Deletion of genomic islands in the Pseudomonas putida KT2440 genome can create an optimal chassis for synthetic biology applications - Peixin Liang (Microbial Cell Factories, 2020)
Abstract Background Genome streamlining is a feasible strategy for constructing an optimum microbial chassis for synthetic biology applications. Genomic islands (GIs) are usually regarded as foreign DNA sequences, which can be obtained by horizontal gene transfer among microorganisms. A model strain Pseudomonas putida KT2440 has broad applications in biocatalysis, biotransformation and biodegradation. Results In this study, the identified GIs in P. putida KT2440 accounting for 4.12% of the total genome size were deleted to generate a series of genome-reduced strains. The mutant KTU-U13 with the largest deletion was advantageous over the original strain KTU in several physiological characteristics evaluated. The mutant KTU-U13 showed high plasmid transformation efficiency and heterologous protein expression capacity compared with the original strain KTU. The metabolic phenotype analysis showed that the types of carbon sources utilized by the mutant KTU-U13 and the utilization capabilities for certain carbon sources were increased greatly. The polyhydroxyalkanoate (PHA) yield and cell dry weight of the mutant KTU-U13 were improved significantly compared with the original strain KTU. The chromosomal integration efficiencies for the γ-hexachlorocyclohexane (γ-HCH) and 1,2,3-trichloropropane (TCP) biodegradation pathways were improved greatly when using the mutant KTU-U13 as the recipient cell and enhanced degradation of γ-HCH and TCP by the mutant KTU-U13 was also observed. The mutant KTU-U13 was able to stably express a plasmid-borne zeaxanthin biosynthetic pathway, suggesting the excellent genetic stability of the mutant. Conclusions These desirable traits make the GIs-deleted mutant KTU-U13 an optimum chassis for synthetic biology applications. The present study suggests that the systematic deletion of GIs in bacteria may be a useful approach for generating an optimal chassis for the construction of microbial cell factories.